1999
DOI: 10.1126/science.283.5408.1712
|View full text |Cite
|
Sign up to set email alerts
|

Ice Core Records of Atmospheric CO 2 Around the Last Three Glacial Terminations

Abstract: Air trapped in bubbles in polar ice cores constitutes an archive for the reconstruction of the global carbon cycle and the relation between greenhouse gases and climate in the past. High-resolution records from Antarctic ice cores show that carbon dioxide concentrations increased by 80 to 100 parts per million by volume 600 ± 400 years after the warming of the last three deglaciations. Despite strongly decreasing temperatures, high carbon dioxide concentrations can be sustained for thousands of years during gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
151
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(175 citation statements)
references
References 20 publications
20
151
0
4
Order By: Relevance
“…It should be noted that the CO 2 concentration increase appears to lag slightly the increase in δD ratio of the ice by 800±600 years at the start of the last glacial termination (Monnin et al, 2001). Studies of the Vostok record found similar lags of around 1000 years at the start of glacial terminations (Caillon et al, 2003;Fischer et al, 1999;Petit et al, 1999). One exception to the exclusion of early glaciations is the minimum before 14.3, which occurs during the early cooling phase between interglacial 15 and glacial stage 14.…”
Section: Depth Markersmentioning
confidence: 87%
“…It should be noted that the CO 2 concentration increase appears to lag slightly the increase in δD ratio of the ice by 800±600 years at the start of the last glacial termination (Monnin et al, 2001). Studies of the Vostok record found similar lags of around 1000 years at the start of glacial terminations (Caillon et al, 2003;Fischer et al, 1999;Petit et al, 1999). One exception to the exclusion of early glaciations is the minimum before 14.3, which occurs during the early cooling phase between interglacial 15 and glacial stage 14.…”
Section: Depth Markersmentioning
confidence: 87%
“…However, and on the Talos Dome (blue diamonds) ice cores (EDC3 synchronized TALDICE-1a age scale) are shown (this study). CO 2 data previously measured on the Vostok ice core are plotted with grey downward pointing triangles after conversion to the EDC3 age scale (Lüthi et al, 2008) for the Petit et al (1999), and with light grey stars for the Fischer et al (1999) CO 2 data. Previous data by Lourantou et al (2010b) are presented with yellow, upward pointing triangles.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Concentrations of atmospheric CO 2 naturally fluctuate between below 200 up to around 280 ppm from glacial to interglacial cycles (Fischer et al 1999), but have risen dramatically in the last 200 years from the 280 ppm post-glacial and pre-industrial levels to modern concentrations of approximately 380 ppm (Feely et al, 2004). Ocean surface water pH has already fallen by 0.1 unit, compared to pre-industrial times, which equals a 30% increase of the H + -concentration (Caldeira and Wickett, 2003).…”
Section: Introductionmentioning
confidence: 99%